2005
DOI: 10.1016/j.ygyno.2005.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of in vitro drug resistance patterns in epithelial ovarian carcinoma

Abstract: Purpose. To compare the in vitro drug resistance profiles of advanced stage primary and recurrent epithelial ovarian cancer specimens using the tritiated thymidine uptake assay.Methods. Extreme drug resistance (EDR) to cisplatin, paclitaxel, 4-hydroxycyclophosphamide, and topotecan was determined for an unselected population of primary and metastatic malignant ovarian tissues, synchronous tumors (primary and metastatic tissues obtained from the same patient at diagnosis), and metachronous lesions (specimens fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…Holloway et al [13 ]reported that women who were treated with agents falling into the EDR category on the basis of in vitro testing had significantly inferior survival compared with women who received agents that showed low drug resistance in vitro. Another study of 119 paired synchronous samples of epithelial ovarian cancer found congruent results for EDR in 89% of cases [14]. Loizzi et al [15] demonstrated a significant survival advantage for ovarian cancer patients who were treated with assay-assisted therapy as compared to empiric treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Holloway et al [13 ]reported that women who were treated with agents falling into the EDR category on the basis of in vitro testing had significantly inferior survival compared with women who received agents that showed low drug resistance in vitro. Another study of 119 paired synchronous samples of epithelial ovarian cancer found congruent results for EDR in 89% of cases [14]. Loizzi et al [15] demonstrated a significant survival advantage for ovarian cancer patients who were treated with assay-assisted therapy as compared to empiric treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not ovarian cancer exhibits tumor heterogeneity before and after chemotherapy, demonstrated in an in vitro drug resistance assay, seems to remain controversial [1][2][3][4]. In the largest analysis of an unselected population with ovarian cancer, there was no significant difference in the proportion of extreme drug resistance (EDR) between primary and recurrent cases [1].…”
Section: To the Editormentioning
confidence: 99%
“…Previous studies by our group demonstrated 25% variation in DNA ploidy between samples from primary tumor and metastases [20], and tumor heterogeneity has been demonstrated between primary tumor and metastatic samples [21] as well as between primary tumor and samples in recurrent OC [22]. In contrast, Tewari et al [23] found no signiWcant diVerence between in vitro drug resistance in primary and metastatic OC lesions, or primary tumors and recurrent samples. Some studies did not report biopsy sites and report inconsistent conclusions [13,24,25].…”
Section: Discussionmentioning
confidence: 74%
“…This suggests that chemotherapy exposure induces in vitro platinum resistance. Previous studies comparing in vitro resistance between samples obtained before and after chemotherapy exposure show inconsistent results [23,24]. In the present study, the amount of residual tumor after surgery may have inXuenced the results as patients unlikely to achieve optimal debulking was selected for neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 75%